Evaluation of machine learning models for solar irradiance prediction (GHI and DNI): a case study in Petrolina, PE, Brazil - Oliveira, Nadja Gomes de (2022)
OLIVEIRA, Nadja Gomes de. Evaluation of machine learning models for solar irradiance prediction (GHI and DNI): a case study in Petrolina, PE, Brazil. 2022. 77 f. Dissertação (Mestrado em Engenharia Mecânica) – Universidade Federal do Ceará, Centro de Tecnologia, Programa de Pós-Graduação em Engenharia Mecânica, Fortaleza, 2022.